Select toxic metals status of pregnant women with history of pregnancy complications in Benin City, South-South Nigeria - OE Otebhi; HB Osadolor (Journal of Applied Sciences and Environmental Management)
Toxic metals are part of the most important groups of environmental pollutants that can bind to vital  cellular components and interfere with their functions via inhalation, foods, water etc. The serum levels  of toxic metals (lead, mercury, cadmium and arsenic) in pregnant women with history of  pregnancy  complications, pregnant women without history of pregnancy complication and  non-pregnant women in Benin City, South – South Nigeria was investigated in this paper, with total of 135 healthy women comprising of 45 pregnant women with history of previous pregnancy  complications, 45 pregnant women without history of pregnancy complications and 45 non-pregnant women without history of pregnancy complications (controls). Some demographic characteristics and 4ml of blood samples were obtained from each subject for the analysis of lead, mercury, cadmium and arsenic by standard methods. Pregnant women with history of pregnancy complications recorded a highly significant increase in the toxic metal (lead) mean value of 25.81μg/dl as against 23.70μg/dl for pregnant women without history of pregnancy complications and 11.23μg/dl for non-pregnant (control) women without history of pregnancy complications as well as significant increases in the mean values of other toxic metals (mercury, cadmium and arsenic) compared with controls (p<0.001). The selected toxic metals (Pb, Hg, Cd and As) may be involved in the development of pregnancy complications among pregnant women in Benin City, South– South Nigeria. Lead in  particular may pose threat to mothers and fetuses as its mean values in the two groups of pregnant women were well above normal. © JASEM